Chapter 9 'Suspect' screening the limits of Britain's medicalised borders, 1962-1981 - Bivins, Roberta (Rethinking borders, 2021)
Like their peers across western Europe, Australia and the Americas, large segments of the British public and a significant proportion of Britain's medical establishment have enthusiastically promoted medical screening (and de facto medical selection) of would-be migrants since World War II. Moreover, from 1962, British law explicitly empowered medical inspection and the exclusion of migrants on health grounds at all three of Britain's idiosyncratic 'medical borders': during entry clearance procedures in their countries of origin; at Britain's ports and airports; and via public health surveillance in the British towns and cities that were the migrants' destinations. However, Britain's geographical and internal borders were largely unmedicalised in the twentieth century and remain comparatively free from specifically medical controls even today. I explore the role of the National Health Service - both as a national symbol and as a physical institution - in shaping and responding to this paradox. Given the intensity of popular suspicions of migrants' bodies and their hygienic and reproductive practices, and the frequency with which medical claims mediated and bolstered anti-migrant rhetoric, why has medical 'control' itself proven politically elusive and persistently suspect?